The Role of Bioinformatics in Personalized Medicine: Your Future Medical Treatment - Margareta Deidre Valeska; Gabriella Patricia Adisurja; Stefanus Bernard; Renadya Maulani Wijaya; Muhammad Aldino Hafidzhah; Arli Aditya Parikesit (Cermin Dunia Kedokteran, 2019)
Bioinformatika berperan sangat penting dalam personalized medicine. Dua metode penting dalam kajian ini adalah randomized algorithm dan computer assisted drug design (CADD). Kajian ini membahas aplikasi, kekurangan, dan masa depan kedua metode tersebut. Saran-saran untuk meningkatkan efek riset bioinformatika dalam kajian personalized medicine juga akan ditelaah.Bioinformatics is beneficial in personalized medicine. Two methods stand out, the randomized algorithm and computer assisted drug design (CADD). This article will discuss the application, pitfalls, and eventual future of those two methods. Suggestion to improve the clarity of the bioinformatics research in the field of personalized medicine will also be reviewed.